HOW TO MEASURE EFFICIENCY OF INFORMATION AND COMMUNICATION TECHNOLOGIES - Evgeny V. Novak (Статистика и экономика, 2016)
Information and communication technologies (ICT) has been actively used in thebusiness. However, whether became easier to understand the effect of their use for a particular organization, not to mention industries, cities, regions, country?Today, with great difﬁculty, you can ﬁnd techniques to enable reasonably accuratecount beneﬁt from the use of equipment,communication channels, software, automated complexes and systems.In this article the author tries to identify practical value assessment of theeffectiveness of ICT (or lack of it), andgive some examples of techniques andmethods inviting to the discussion ofeconomists, industry experts, investors.